METAFORA PADA LIRIK LAGU SOUNDTRACK ANIME GUILTY CROWN - Marsella, Elin; Isnaini, Zuli Laili; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discusses the types of categories and analysis of metaphorical meanings contained in the lyrics of anime anime soundtrack Guilty Crown. The purpose of this study is to determine the type of category and the meaning of the metaphor in the lyrics of anime soundtrack Guilty Crown. The object of this study is four songs of anime soundtrack Guilty Crown. This is a quantitative study with with descriptive method. The result of study found eleven metaphorical expressions and type of categories as human, living, object, substance, energy, cosmic, and beimg. The categories of animate and terrestrial beings are not found in this study. In addition, this study uses association techniques in determining the meaning of metaphor.Key Word : Metaphors, Lyric, Soundtrack, Anime, Guilty Crown